The Economic Determinants of Systematic Risk: Discussion - Fisher, Lawrence (Journal of Finance, 1974)
Lawrence Fisher, The Economic Determinants of Systematic Risk: Discussion, The Journal of Finance, Vol. 29, No. 2, Papers and Proceedings of the Thirty-Second Annual Meeting of the American Finance Association, New York, New York, December 28-30, 1973 (May, 1974), pp. 488-492